Change of direction demands in German high-performance soccer - Deutsch, J.; Rieke, M.; Rein, R.; Held, S.; Donath, L. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: This study aimed to compare the change of direction (COD) demands of German Bundesliga soccer match play relative to playing position using an optical-tracking-system. COD data were collected from German Bundesliga soccer teams (2017-2018 season; 17 matches). The findings of this study would give further insights into soccer match play demands and could therefore influence load management, physical training and rehabilitation process of soccer practitioners.